2007
DOI: 10.1590/s0100-54052007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da solarização do solo, seguida pela aplicação de Trichoderma spp: ou de fungicidas, sobre o controle de Pythium aphanidermatum e de Rhizoctonia solani AG-4

Abstract: O presente trabalho foi realizado com o objetivo de estudar alternativas para a desinfestação de solos, especialmente considerando a retirada do brometo de metila do mercado. Avaliou-se o efeito da solarização do solo, seguida ou não pela aplicação de isolados de Trichoderma spp. ou de fungicidas, sobre o controle de Pythium aphanidermatum e de Rhizoctonia solani AG-4, responsáveis por tombamento e podridão de raízes em várias culturas. Dois experimentos foram realizados em Piracicaba, SP (latitude 22º 42' e l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
2
1
0
Order By: Relevance
“…These treatments prove to be the most effective since the temperatures generated by these months were the highest according to the average test performed previously. The information obtained coincides with the results of [18,30], found that many soil pathogens do not survive during exposure 6 hours at 47°C and 2 to 4 weeks if the temperature is 37°C.…”
Section: Interpolationssupporting
confidence: 87%
See 1 more Smart Citation
“…These treatments prove to be the most effective since the temperatures generated by these months were the highest according to the average test performed previously. The information obtained coincides with the results of [18,30], found that many soil pathogens do not survive during exposure 6 hours at 47°C and 2 to 4 weeks if the temperature is 37°C.…”
Section: Interpolationssupporting
confidence: 87%
“…On the other hand [36,37] indicate in composting studies, that the temperatures reached were of 60°C and they were sustained during three weeks, these were enough to kill these miroorganimos, However, there is the possibility of an undetectable population growth, due to the heterogeneity of composting in the piles. Similar patterns were reported by [30] in a study to determine the temperature that inactivates the movement of the bacterium salmonella enteritidis PT4 notes that this occurred at 60°C [35] notes that the E. coli bacterium that developed in culture medium and under laboratory conditions, its inactivity occurred after 15 minutes at temperatures of 60°C (Table 5).…”
Section: Identification and Conclusionsupporting
confidence: 73%
“…Gomes et al (2009) found Fusarium contaminating soybean seeds collected from different sites and this was related to the host cultivar. The biological product is composed of Trichoderma, a fungus much used for the biological control of other fungi (Patrício et al, 2007). It is interesting to note that Trichoderma was detected on only three Lyra cultivar seeds whereas a higher number of AL Guarany 2002 seeds had this fungus, suggesting that the Lyra seeds did not favor Trichoderma colonization.…”
Section: Resultsmentioning
confidence: 99%